Ti, Ni, and TiNi alloys in the generation of THz pulses and their use in bolometers - Lubenko, Dmitry M.; Losev, Valery F.; Andreev, Yury M. 1946-; Denisov, Vladimir V. канд. техн. наук; Shugurov, Vladimir V.; Ezhov, Dmitry M.; Svetlichnyi, Valerii A. (Bulletin of the Russian Academy of Sciences: Physics)
A study is performed of the generation of ultrashort THz pulses in Ti, Ni, and TiNi plates, compared to Au, Ag, Cu plates. The possibility of using them as photosensitive materials in bolometers is considered. Such sources can be used in atmosphere monitoring systems. @ 2019, Allerton Press, Inc.